Media and political framing of crystal methamphetamine use in Australia. (3rd July 2020) - Cohn, Amanda; O'Connor, Rosslyn; Lancaster, Kari; Rawstorne, Patrick; Nathan, Sally
Abstract: Media and politicians both influence public opinion and policy responses to illicit drug issues. This study examines the contribution each may have made in Australia in 2015 to the problem and politics streams of the policy process, as outlined in Kingdon's 'multiple streams' heuristic, when a National Ice Taskforce responded to increased public, political and media concern about methamphetamine use. A retrospective content analysis compared the frequency and content of articles about methamphetamine in print media ( N = 639) and federal parliament speeches ( N = 158) in 2015. Peaks in the number of media articles and debates in parliament followed the establishment and interim findings of the Ice Taskforce. The findings showed that politicians more frequently framed methamphetamine use as a crisis or epidemic than the media. Both frequently portrayed cost to society as the consequence of methamphetamine use and often cited law enforcement sources. The media most frequently positioned methamphetamine users as criminal or deviant compared to politicians who did not position the user or positioned them as an addict or victim. This analysis highlights the convergence of the problem and politics streams and suggests they are not independent as first posited by Kingdon.